Relationship of Work Quality, Quantity, Timeliness, Effectiveness, and Independence on Public Service Performance in Kampong Trabaek District Administration, Prey Veng Province, Cambodia - Serey, Mardy; J. Girao, Michael (Journal of Public Administration and Government, 2025)
This study looks into the variables affecting public service performance (PSP) in Kampong Trabaek District Administration, Prey Veng Province, Cambodia. Although district-level public service delivery is essential to good governance, it continues to face obstacles like inefficiency, corruption, and a lack of funding. Work quality (WQ), work quantity (WT), timeliness (TI), effectiveness (EF), and independence (ID) are the five main dimensions that are examined in this study along with how they interact with PSP. This study aims to explore the current status of PSP in Kampong Trabaek District Administration and to investigate the relationship between WQ, WT, TI, EF, and ID in shaping PSP within Kampong Trabaek District Administration, Prey Veng Province, Cambodia. To systematically investigate these relationships, data were gathered from 91 district administration stakeholders and employees using a quantitative research design with descriptive and correlational analysis. The questionnaire in the form of Likert scale was the instrument used in this study. The results provide subtle insights into the roles that each dimension plays in PSP. Timeliness and independence showed a strong positive relationship with work quality, underscoring the value of high standards in encouraging responsiveness and accountability. Effectiveness and work quantity were found to be significantly correlated, highlighting the need for a balance between productivity and reaching desired results. Timeliness was found to be a crucial component that was closely related to every other aspect, highlighting its function in boosting public trust in government. Effectiveness was essential to guaranteeing fair service distribution and flexibility in times of emergency, while independence allowed local leaders to develop context-sensitive solutions but also revealed weaknesses in supervision and resource distribution. To sum up, this study emphasizes how crucial it is to take a comprehensive approach to PSP, balance operational aspects, and promote collaborative governance models in order to attain long-lasting enhancements in Kampong Trabaek District Administration's public service delivery.